Akibat Hukum Perkawinan tidak Tercatat terhadap Legalitas Anak di Dsn Tanjung Desa Taman Jrengik Sampang - Laila Nadia; Sumriyah Sumriyah (Referendum : Jurnal Hukum Perdata dan Pidana, 2024)
Marriage is a human right, as stated in Article 28B paragraph (1) of the Second Amendment to the 1945 Constitution, and marriage is explicitly regulated in Law No. 1 of 1974 on Marriage. Article 2 of the Marriage Law states that marriage must be registered according to the applicable laws and regulations. However, this cannot be fully implemented throughout Indonesia, especially in the Dsn Tanjung area, Taman Kec Jrengik Sampang. One of the factors preventing full implementation is that marriages are conducted underage. This research uses an empirical research approach, also known as field research. The purpose of this method is to investigate the applicable legal provisions and their implementation in society. The research results show that children born from unregistered marriages face difficulties in obtaining civil status and legal certainty.